Retrospective analysis of uterine sarcoma cases managed by a single institute - Yahaya, Ahmad Shuib; Mohd Abas, Mohd Norazam; Omar, Jamil (Farname, 2025)
Background & Objective: This study aims to analyze the survival outcomes and prognostic factors of patients with uterine sarcoma in the Department of Gynae-Oncology, between June 2015 and December 2022. Materials & Methods: The study population consists of patients with histopathologically confirmed uterine sarcoma. The oncological data collected includes stage, pathological report, date and type of surgery, adjuvant therapy, recurrence, and mortality. Kaplan-Meier analysis used to estimate survival. Results: We identified 58 eligible uterine sarcoma patients: 13 leiomyosarcoma (22.4%), nine endometrial stromal sarcoma (15.5%), 32 carcinosarcoma (55.2%), two adenosarcoma (3.4%) and another two were undifferentiated sarcoma (3.4%). Mean age was 56.1 (SD=12.03) and 56% of patients were postmenopausal. Majority of patients presented in stage III and IV (53.4%) and only 22 patients (37.9%) in stage I. Adjuvant radiotherapy was given to 21 patients (36.2%); eight patients (13.8%) received chemotherapy, and nine patients (15.5%) received both radiotherapy and chemotherapy. The median follow-up period was 13.5 months (range: 73 months) and total of 35 patients (60.3%) had recurrence with median time to recurrence of 6.0 months (range: 35). Death occurred in 21 patients (36.2%) with median time to death 5.0 months (range: 36 months). Progression free survival (PFS) among all patients was 26.64 (range: 4.32) months with significant correlation with stage of disease. Overall survival (OS) in patients received surgery only, radiotherapy and combined radiotherapy and chemotherapy were 23.3, 54.8 and 62.4 months respectively (P. value 0.03). Conclusion: Uterine sarcoma is a relatively rare tumor type with poor survival. Multimodality adjuvant treatments were shown to improve prognosis in those patients.